Importance Of Vata Dosha And Its Aatma Roopas (Cardinal Symptoms) In Maintaining Health And Balance In Life - Kachhawaha, Shilpa; Sharma, Rajesh Kumar; Sharma, Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda, The Science of Life is often called as The Mother of All Healing. It emphasizes on preventive techniques and encourages the maintenance of health through which sukha (happiness) can be attained and dukha(miseries) can be abolished. According to Ayurveda everything which exist in universe is made up of Panchmahabutas(the five elements) Aakash, Vayu, Tejas, Jala, Prithvi. Therefore, every concept of Ayurveda is predicted and described on the basis of Panchmahabhutas. The Tridoshas(vata, pitta, kapha), one of the basic pillars of Ayurveda represent the presence of Panchmahabhuta in our body. These are the primary functional energies in our body that our aligned with the elements of nature. Similarly, Doshas are the main essential contributory factors for the causation of disease. No disease manifests without the participation of Doshas in the samprapti(pathogenesis). Among the three basic humors, Vata plays an important role for establishing equilibrium of health in our body. This is because no activity in our body occurs without involvement and motivation of Vata Dosha. Thus, Vata is master of all the activities in human body. Hence in this article an attempt has been made to understand the physiological properties(Gunas) and cardinal symptoms(Aatma roopas) of Vata Dosha.